Improving pedal power during semireclined leg cycling. - Trumbower, R.D (IEEE Engineering in medicine and biology magazine)
Using time-sequence analysis of EMG measurements to determine if changes in muscle activation timing, sequencing, and stimulation can improve pedaling effectiveness.